Perbedaan Hasil Padi Antarmusim di Lahan Sawah Irigasi - Satoto Satoto; Yuni Widyastuti; Untung Susanto; Made Jana Mejaya (Iptek Tanaman Pangan, 2013)
Indonesia as a tropical country, has two distinct planting seasons, i.e. rainy (WS, October-April) and dry season (DS, May-September). The difference between the two seasons include the amount of rainfall, air temperature, humidity, solar radiation, and cloudiness which cause yield gap between seasons. Rice yield testing at various locations and seasons using inbred and hybrid varieties showed the occurrence of yield gap patterns. In East Java during the 2001-2003 testing showed inconsistence yield gap between planting seasons across locations. Testing of 29 very early maturing accessions in Kuningan (550 m asl) during DS 2010 and WS 2010/2011 showed no significant yield gap between planting seasons. Similarly, testing of 10 GSR inbred lines along with four check varieties during DS 2012 and WS 2012/2013 showed no significant yield gap due to seasons, genotypes, and plant spacing. Factors which presumably affected the yield gap include air temperature, CO2 concentration, and solar radiation during grain filling period. Increasing temperature had reduced the grain yield, where as increasing CO2 concentration increased plant biomass formation, while optimum solar radiation during grain filling increased grain yield. To reduce yield gap between seasonal planting, the more readily observable causing the yield gap should be anticipated, such as: pests and diseases in each season for each location, assigning suitable variety for specific location and planting season, and application of most appropriate cultivation techniques for each location and season (fertilizers application, plant spacing, irrigation, and pest/diseases management).